Radiometry in modern scientific experiments - Pravilov, A. M. (Springer, 2011)
he reader is provided with information about methods of calibration of light sources and photodetectors as well as responsiveness of spectral instruments  ranging from near infrared to vacuum UV spectral, 1200 ? 100 nm, and radiation intensities of up to several quanta per second in absolute and arbitrary units. The author describes for the first time original methods of measurements they created and draws upon over 40 years of experience in working with light sources and detectors to provide accurate and precise measurements. This book is the first to cover these aspects of radiometry and is divided into seven chapters that examine information about terminology, units, light sources and detectors, methods, including author?s original ones, of absolute calibration of detectors, spectral instruments responsiveness, absolute measurements of radiation intensity of photoprocesses, and original methods of their study. Of interest to researchers measuring; luminescence spectra, light intensities from IR to vacuum UV, spectral range in wide-light intensity ranges, calibrate light sources and detectors, absolute or relative quantum yields of photoprocess determination.